Rethinking taxon sampling in the light of environmental sequencing - Henrik Nilsson, R; Ryberg, Martin; Sjökvist, Elisabet; Abarenkov, Kessy (Cladistics, 2011)
Environmental DNA sequencing efforts of substrates such as soil, wood, and seawater have been found to present very different views of the underlying biological communities compared with efforts based on morphological examination and culture studies. The taxonomic affiliation of many of these environmental sequences cannot be settled with certainty due to the lack of proximate reference sequences in the corpus of public sequence data, and they are typically submitted to the international sequence databases without much indication of their relatedness. The scientific community has proved reluctant to include such unnamed sequences in phylogenetic analyses and taxonomic studies, but the present study shows such a position to be not only largely unwarranted but also potentially unsound. The sequences of 48 published fungal alignments of the nuclear ribosomal internal transcribed spacer region were subjected to similarity searches in the sequence databases to recover environmental sequences with a clear bearing on the respective ingroup. An average of 20 environmental sequences were added to each alignment, and upon rerunning the phylogenetic analyses of each study we found that topological rearrangements involving the original ingroup sequences were observed for no less than 29 (60%) of the studies. In nearly 20% of these cases, the rearrangements were large enough to question or even overthrow at least one conclusion presented in the original studies. The basal branching order was similarly subject to changes in 16% of the applicable studies. Environmental sequences are thus not only relevant in ecological research but form a requisite source of information also in systematics and taxonomy. © The Willi Hennig Society 2010.